Physiologically-Based PK/PD Modelling of Therapeutic Macromolecules - Thygesen, Peter; Macheras, Panos; Van Peer, Achiel (PHARMACEUTICAL RESEARCH, 2009)
Therapeutic proteins are a diverse class of drugs consisting of naturally occurring or modified proteins, and due to their size and physico-chemical properties, they can pose challenges for the pharmacokinetic and pharmacodynamic studies. Physiologically-based pharmacokinetics (PBPK) modelling has been effective for early in silico prediction of pharmacokinetic properties of new drugs. The aim of the present workshop was to discuss the feasibility of PBPK modelling of macromolecules. The classical PBPK approach was discussed with a presentation of the successful example of PBPK modelling of cyclosporine A. PBPK model was performed with transport of the cyclosporine across cell membranes, affinity to plasma proteins and active membrane transporters included to describe drug transport between physiological compartments. For macromolecules, complex PBPK modelling or permeability-limited and/or target-mediated distribution was discussed. It was generally agreed that PBPK modelling was feasible and desirable. The role of the lymphatic system should be considered when absorption after extravascular administration is modelled. Target-mediated drug disposition was regarded as an important feature for generation of PK models. Complex PK-models may not be necessary when a limited number of organs are affected. More mechanistic PK/PD models will be relevant when adverse events/toxicity are included in the PK/PD modelling.
Keywords: convective distribution; Cyclosporin A; erythropoietin; interspecies scaling; macromolecules; monoclonal antibodies; natural cell lifespan concept; neonatal Fc receptors; non-linear pharmacokinetics; permeability-limited distribution; physiologically-based pharmacokinetic modelling; PK/PD modelling; target-mediated drug disposition